European Co-Operation through "Interactive Storytelling" in the European Virtual Training College - Harnischmacher, Christoph; Rauter, Ulrich (Proceedings of the International Conference on Networked Learning, 2000)
This article on the SOCRATES project "CJ. Communication, Collaboration, Community Development - Impacting Education in Networked Learning for Disadvantaged Young People" focuses especially on the relationship between Open Learning and Lernzielorientierter Unterricht in a European collaboration process. It highlights the question of compatibility of virtual classrooms and real classrooms in a learning and teaching culture of disadvantaged youths and their teachers. Looking back on our project that started at the end of ’98 we try to describe a few discoveries. Project partners from Germany, Great Britain, Italy, Spain, the Netherlands and the Czech Republic are working together in the CJ project addressing directly teachers who are working with disadvantaged young people. It tries to develop a method of Open and Distance Leaming, "Interactive Storytelling", that reflects the special needs of our target groups and the different styles of teachers. Main aims are: Development of ODL for youth at risk Focus on active use of Multimedia and Internet as communication and production environments Establishing a European working context between institutions supporting youth at risk Empowering teachers to link the real classroom with virtual classrooms